Sulphur‐Embedded Hydrocarbon Belts: Synthesis, Structure and Redox Chemistry of Cyclothianthrenes. Issue 34 (16th July 2021) - Wang, Shenghua; Yuan, Jun; Xie, Jialin; Lu, Zonghuan; Jiang, Long; Mu, Yingxiao; Huo, Yanping; Tsuchido, Yoshitaka; Zhu, Kelong
Abstract: Cyclothianthrenes, a series of sulphur‐embedded hydrocarbon belts proposed a decade ago, were successfully constructed through a stepwise bottom‐up synthesis. The belt [6]cyclothianthrene ([6]CT ) is the smallest and most strained member of the family yet reported. Both [6]CT and [8]CT are the first examples of cyclothianthrene characterized by single crystal X‐ray diffraction. An unprecedented chiral belt [7]CT and a Möbius‐shaped [9]CT were also achieved via modular synthesis. Crystallographic and computational studies show that belts [6]CT‐ [8]CT have prism‐like conformations with well‐defined tubular cavities which have potential for guest molecule inclusion. Cyclic voltammograms further revealed that these belts are redox‐active. The success of constructing sulphur‐embedded hydrocarbon belts, that is, cyclothianthrenes, greatly enriches the chemistry of heteroatom‐doped molecular belts and tubes. Abstract : A family of sulphur‐embedded hydrocarbon belts, [ n ]cyclothianthrenes, were successfully constructed and characterized. The reported synthetic strategy allows access to not only the smallest and most strained cyclothianthrene, but also unprecedented chiral belts including a Möbius strip. Further studies reveal these belt‐like molecules are redox‐active and potential materials for host‐guest chemistry.